The Neuroscience of Cocaine 2017
DOI: 10.1016/b978-0-12-803750-8.00040-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunctions in Chronic Cocaine Users

Abstract: After nearly three decades of research, there is still no clarity on the causal relationship between chronic cocaine use and cognitive functioning. However, the current literature consistently suggests that broad cognitive impairments occur in not only dependent cocaine users but also recreational cocaine users, with impairments involving attention, working memory declarative memory and executive functions. Moreover, it was recently shown that chronic cocaine users exhibit specific deficits in sociocognitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
1
7
0
1
Order By: Relevance
“…As consistently shown by previous studies 12,24,27,28 , we found that the SCD and ICD groups exhibited EF impairments in comparison with CTR. Here, we specifically addressed the route of administration, showing that subjects in the SCD group exhibited overall more profound deficits compared to the ICD group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As consistently shown by previous studies 12,24,27,28 , we found that the SCD and ICD groups exhibited EF impairments in comparison with CTR. Here, we specifically addressed the route of administration, showing that subjects in the SCD group exhibited overall more profound deficits compared to the ICD group.…”
Section: Discussionsupporting
confidence: 91%
“…However, while the ICD group presented a trend towards the impairment of memory-related processing, then SCD group showed a stronger attentional deficit. The relative importance of executive, attentional and memory domains has been controversial in the neuropsychological study of cocaine consumption 12,24,27,28 . We suggest that these inconsistencies could arise due to incomplete matching 10 of critical variables (such as SES), polyconsumption 13 , and most critically by differences in the route of administration 12,24,27,28 , possibly the most under-investigated factor in the current literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we also found clear cocaine but no pronounced levamisole effects in the domains of attention and working memory but a significant levamisole effect on executive functions. Thus, one might speculate that at least some of the reported discrepant findings in the newer literature regarding executive function impairments 41 might be explained by differences in recent levamisole exposure. As levamisole was proposed to be metabolized into the amphetamine-like stimulant aminorex and other metabolites 1 , 6 , 7 , and previous reports showed pronounced executive function decrements in chronic amphetamine users 42 , 43 , the present effect might not be linked to levamisole alone but also to its metabolic products.…”
Section: Discussionmentioning
confidence: 95%
“…While some studies investigated the linkage between these neurocognitive deficits and cocaine abstinence (6), only one study yet investigated the longitudinal relationship between cognitive impairments and changing cocaine use (7). In sum, these studies indicate that basal cognitive deficits in cocaine users seem to be largely drug-induced, remain stable during the first weeks of abstinence but likely improve after some months (8).…”
Section: Introductionmentioning
confidence: 91%